(3fXGe SfO GdTjNjfs - (3YHO GdSdGe GdbGOQjs
(3ChdgG (B:s
(3GdMeO ddg gPG fXGe SfO GdTjNjf CYfi Gdhdjjf s
(3BNQgG (B:s
(3hCef YdjfG HLhGQ GdeUWai jG NjQ ef CYWi hNjQ ef hbi EfJgJ HMeO Gddg hMSf Yhfg hUdi Gddg Ydi SjOfG eMeO hBdg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3HBNQgG fbhd TYQjIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(489 (3O(B) s
Keywords: (3GdeLGejYs